Guru Kristen Sebagai Pembangun Relasi Dalam Membentuk Aspek Sosial Siswa Di Era Pandemi - Felisya Sofyanti Marbun; Wiyun Philipus Tangkin (Institut Agama Kristen Negeri Toraja, 2022)
The existence of students as the image of God, also a reflector of God, one of which is related. As social beings, students are expected to be able to relate to each other. The fact is, there are still students who are antisocial, especially due to the use of gadgets. In this case, Christian teachers play a role in shaping the social aspects of students. So that, the purpose of writing this paper is the role of Christian teachers as relationship builders in shaping the social aspects of students in the pandemic era. The research method used is literature study. Therefore, Christian teachers need planning in learning related to the internalization of social values, student social interaction activities, and classroom arrangements. In the era of the pandemic, Christian teachers must be wise and creative in using technology to build relationships in the classroom. In conclusion, Christian teachers play a very important role as relationship builder in the classroom, so that students can relate to each other. Suggestions for Christian teachers are to improve their skills in building relationships, especially in the era of the pandemic and realize that they are God's co-workers so they need to rely on God. Keberadaan siswa sebagai gambar dan rupa Allah, juga merupakan reflektor Allah, salah satunya dengan berelasi. Sebagai makhluk sosial, siswa diharapkan mampu berelasi terhadap sesamanya. Fakta yang terjadi masih terdapat siswa yang bersikap antisosial terutama akibat penggunaan gadget. Dalam hal ini, guru Kristen berperan dalam membentuk aspek sosial siswa. Berdasarkan hal tersebut, tujuan penulisan makalah ini adalah memaparkan peran guru Kristen sebagai pembangun relasi dalam membentuk aspek sosial siswa di era pandemi. Metode penelitian yang digunakan adalah studi literatur. Guru Kristen berperan sebagai pembangun relasi dalam membentuk aspek sosial siswa. Oleh karena itu, guru Kristen memerlukan perencanaan dalam pembelajaran terkait internalisasi nilai sosial, aktivitas interaksi sosial siswa, dan pengaturan kelas. Di era pandemi, guru Kristen harus bijaksana dan kreatif dalam menggunakan teknologi guna membangun relasi dalam kelas. Kesimpulannya, guru Kristen sangat berperan sebagai pembangun relasi di kelas, agar siswa dapat berelasi terhadap sesama. Saran bagi guru Kristen adalah meningkatkan keterampilannya dalam membangun relasi terutama di era pandemi dan menyadari bahwa dirinya adalah rekan sekerja Allah sehingga perlu mengandalkan Allah.